Lithospheric shear velocity structure of South Island, New Zealand, from amphibious Rayleigh wave tomography. Issue 5 (23rd May 2016) - Ball, Justin S.; Sheehan, Anne F.; Stachnik, Joshua C.; Lin, Fan‐Chi; Yeck, William L.; Collins, John A.
Abstract: We present a crust and mantle 3‐D shear velocity model extending well offshore of New Zealand's South Island, imaging the lithosphere beneath the South Island as well as the Campbell and Challenger Plateaus. Our model is constructed via linearized inversion of both teleseismic (18–70 s period) and ambient noise‐based (8–25 s period) Rayleigh wave dispersion measurements. We augment an array of 4 land‐based and 29 ocean bottom instruments deployed off the South Island's east and west coasts in 2009–2010 by the Marine Observations of Anisotropy Near Aotearoa experiment with 28 land‐based seismometers from New Zealand's permanent GeoNet array. Major features of our shear wave velocity ( Vs ) model include a low‐velocity ( Vs  < 4.4 km/s) body extending from near surface to greater than 75 km depth beneath the Banks and Otago Peninsulas and high‐velocity ( Vs ~4.7 km/s) mantle anomalies underlying the Southern Alps and off the northwest coast of the South Island. Using the 4.5 km/s contour as a proxy for the lithosphere‐asthenosphere boundary, our model suggests that the lithospheric thickness of Challenger Plateau and central South Island is substantially greater than that of the inner Campbell Plateau. The high‐velocity anomaly we resolve at subcrustal depths (>50 km) beneath the central South Island exhibits strong spatial correlation with upper mantle earthquake hypocenters beneath the Alpine Fault. The ~400 km long low‐velocity zone we image beneath eastern South Island and the inner Bounty Trough underlies Cenozoic volcanics and the locations of mantle‐derived helium measurements, consistent with asthenospheric upwelling in the region. Key Points: Surface shear wave velocity model onshore and offshore South Island, NZ Thin, low‐velocity lithosphere beneath inner Campbell Plateau Thick, high‐velocity lithosphere west of Alpine Fault